Assessment of Stratified Speed Characteristics and Compliance with Posted Speed Limit in an Urban Area: A Case Study of Section of Karnali Highway, Nepal - Bist, Trilok Chandra; Tiwari, Hemant (International Journal on Engineering Technology, 2024)
Speed is the fundamental element of traffic engineering which is related to safety, time, comfort, convenience, and economics of the transportation system. Speed tends to reduce while the vehicles enter the urban areas even within the highway. Urban areas even have posted speed limits to control the speed characteristics, but the obeyance of the posted limit is still questionable. This research examines the speed characteristics of various means of transportation within urban areas. Section of roads within urban areas of Surkhet district along Karnali Highway (NH58) is considered as a study area and a manual method of data collection was adopted. The stratified samples of speed covering all means of transportation were collected during off-peak hours. Even a small section of roads has varying speed limits ranging from 20 to 40kmph. The collected data were used to calculate different kinds of speeds for each category of vehicles and further combined based on volume proportion to come up with average speed. The road is divided into four lanes, which motivates speeding, and it was observed the average speed of 2-wheelers, cars, and utility vehicles was between 30-40kmph. Data assessment shows the average speed limit was within 40kmph, which is legally mandated by the Motor Vehicle and Transport Management Act 2049, which is even taught during the process of licensing to drivers. Hence, the installation of other speed limit signs needs proper education and awareness followed by proper enforcement techniques for effective implementation of the posted speed limit.